1992
DOI: 10.1128/jcm.30.5.1262-1266.1992
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Aeromonas strains to the genospecies level in the clinical laboratory

Abstract: One hundred thirty-three strains of Aeromonas (human, n = 102; animal, n = 16; environmental, n = 15) previously identified to the DNA group level by molecular methods were biochemically analyzed for 58 properties. On the basis of the use of between 9 and 16 selected tests, 132 of the 133 strains (99%o) could be assigned to their correct hybridization group using this biochemical scheme. The results suggest a feasible approach for identifying aeromonads to genospecies level under appropriate conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
61
0
4

Year Published

1998
1998
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(70 citation statements)
references
References 21 publications
(24 reference statements)
5
61
0
4
Order By: Relevance
“…cephalotin. Similar results have been reported for this species by other authors (Altwegg et al 1990 ;Altwegg and Lüthy-In conclusion, the results of this study show that only a few phenotypic tests are useful for distinguishing Aeromonas Hottenstein 1991 ; Abbott et al 1992 ;Kämpfer and Altwegg 1992 ;Hänninen and Siittonen 1995). However, contrary to genomic species isolated from different sources.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…cephalotin. Similar results have been reported for this species by other authors (Altwegg et al 1990 ;Altwegg and Lüthy-In conclusion, the results of this study show that only a few phenotypic tests are useful for distinguishing Aeromonas Hottenstein 1991 ; Abbott et al 1992 ;Kämpfer and Altwegg 1992 ;Hänninen and Siittonen 1995). However, contrary to genomic species isolated from different sources.…”
Section: Discussionsupporting
confidence: 91%
“…Hottenstein (1991), Abbott et al (1992), Kämpfer and ----------------------------------------------------------------------- ------------------------------------------------------------------------ ---------------------------------------------------------------------- ------------------------------------------------------------------------ , Carnahan and Joseph (1993), Hänninen and lake water. Altwegg et al (1990) and Janda et al (1996) have suggested that infection resulting from environmental Siittonen (1995).…”
Section: Discussionmentioning
confidence: 99%
“…Typing and intra-specific diversity studies require phenotypic and genetic tests [2,9,41] for an unequivocal strain identification to species level. Several previous typing and molecular epidemiological studies of A. hydrophila populations did not include a genetic method to confirm the identity of the strains [13,18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Suspect colonies from the selective agars were identi®ed as previously described (Furniss et al 1979;Carnahan et al 1991;Abbott et al 1992;Janda et al 1995;McLaughlin 1995).…”
Section: Discussionmentioning
confidence: 99%